Principal’s Leadership in Improving Teachers’ Performance - Saronto, Saronto (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to describe the principal’s leadership in improving teacher performance at SD Negeri 1 Kali Deras, as well as the supporting and inhibiting factors of the Principal’s leadership in improving the quality of teacher performance. Through a qualitative case study approach, this study aims to describe in detail the perspective of the Principal’s leadership in improving teacher performance. This study uses observation, interviews, and document studies to collect data. The data obtained were then analyzed through the process of reduction, presentation, and drawing conclusions. Data validity testing was carried out using triangulation techniques. The results of this study indicate that: 1) The principal’s leadership is quite good in improving teacher performance. They provide coaching, supervision, encouragement or motivation, and evaluation of teacher performance. The assessment of teacher performance shows quite satisfactory results, especially in planning, implementing, and evaluating learning; 2) the supporting factor is the strong support and motivation from the principal. Meanwhile, the inhibiting factors include the lack of Liquid Crystal Display (LCD) projectors and internet access, minimal teacher skills in managing classes and using various learning methods, and lack of discipline among teachers. The research results recommend that principals make improvements and provide guidance to teachers, so that the principal’s leadership in improving teacher performance can be implemented optimally.